Pemberdayaan Dan Peningkatan Ekonomi Masyarakat Melalui Program Bank Sampah Dusun Dayakan Kulon, Semanu, Gunung Kidul - Saputra, Moh Riza; Nurramadhani, Hilman; Az Zahra, Alif Balqis; Pramesty, Anggita Putri; Safira, Assyifa Prita; Saputro, Azis; Widyantara, Anindita Rafif; Maftuh, Muhammad; Jallow, Adama Sheriff; Anggita, Zahrina; Setiawan, Asep (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
One of the problems in Dayakan Kulon Hamlet, Dadapayu Village, Semanu District, Gunungkidul Regency, is the habit of people burning garbage which contributes to air pollution and health problems. In addition, an environment that is not well managed becomes a breeding ground for the aedes aegypti mosquito, increasing the risk of Dengue Fever (DBD). As a form of contribution to handling this problem, the community service program of the University of Muhammadiyah Yogyakarta (UMY) collaborates with the Village Government, environmental activists, and the private sector to develop an organization-based waste management system. This program begins with the formation of a waste bank starting with socialization and education, followed by the formation of a management based on legality. As an effort to support operations, facilities are provided such as trash bins, trash bags, sacks, scales, savings books, administration books, making official logos and WhatsApp groups. Furthermore, a Focus Group Discussion (FGD) is held with cadres and community leaders to determine the allocation of funds and strategic locations for waste collection in each RT. Sorting and weighing are carried out at the hamlet hall. This program aims to increase public knowledge and awareness regarding waste management. This program also collaborates with collectors as partners in waste recycling and provides training for waste management cadres so that they have the skills to process waste into products of economic value. The results of this program show an increase in public awareness in waste management, reduced waste burning practices, and increased environmental cleanliness. The implementation of this organization-based waste management system is expected to be a sustainable solution in maintaining environmental health and improving the welfare of the Dayakan Kulon Hamlet community and its surrounding areas